Model Pembelajaran Classroom Community Partnership (CCP) Dalam Pembelajaran PPKn - Lisye Salamor (Inovasi Kurikulum, 2015)
Classroom Learning Community Partnership Model (CCP) as an innovative learning product iiseful in integrating a variety of learning resources in civic education at primaty schools. Research and development method in the process ofdeveloping the model, has proven successful in improving the social cognitive skills with parents involvment as a the source and models a of of learning in the learning process.